NH3 Competitive Adsorbed FTIR: A Potential Method to Investigate the Confined Species‐Acidic Sites Interaction in SAPO‐34 Catalyst. Issue 17 (25th October 2016) - Hu, Bing; Wang, Dakang; Gao, Simeng; Zhang, Xiangwen; Mao, Guoliang; Wang, Baohui; Luo, Mingjian
Abstract: NH3 competitive adsorbed FTIR method is proposed for investigating the interaction between confined species and acidic sites. Results indicate aromatic cations formed in SAPO‐34 cages. The cations have much higher extinction coefficient than the corresponding aromatics. They cause the new absorbance bands between 1300 and 1700 cm −1 . The absorbance bands at 1615 and 1607 cm −1 are related to the vibration of strengthened C=C bonds of aromatic cations. The area of these two bands can be used to quantify the amount of confined species. The band at 1650 cm −1 is a sign of the formation of phenanthrene derivatives and pyrene. Abstract : NH3 competitive adsorption FTIR method is proposed for investigating the confined species‐acidic sites interaction. The interaction between aromatics and acidic sites leads to the formation of cationic species. These cations are much more infrared active than the original aromatic molecules. The absorbance bands at 1615 and 1607 cm −1 are related to the vibration of strengthened C=C bonds of aromatic cations. The band at 1650 cm −1 is a sign of the formation of phenanthrene derivatives and pyrene.